Pengaruh Lingkungan Kerja, Gaya Kepemimpinan dan Efikasi Diri terhadap Keterikatan Karyawan (Studi pada PT Wisata Titiannusantara Pelangi Al Malik Travel Jakarta Barat) - Anindya Nurhaliza; Zulvia Khalid (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Employee engagement is a crucial factor in improving individual performance and organizational success. Companies with a high level of employee engagement tend to create a positive, productive, and sustainable work environment. This study aims to analyze the impact of work environment, leadership style, and self-efficacy on employee engagement at PT Wisata Titiannusantara Pelangi (Al Malik Travel) West Jakarta. This research uses a quantitative approach with a survey method. The sampling technique used is non-probability sampling with a saturated sample method, involving 40 respondents out of the total population of 41 permanent employees. The research instrument is a Likert scale questionnaire, supported by observations and literature study. The data were analyzed using SPSS version 30 and Microsoft Excel 2006 with multiple linear regression analysis techniques. The results indicate that work environment and leadership style have no significant effect on employee engagement, while self-efficacy has a positive and significant impact on employee engagement. The coefficient of determination (R²) value of 0.876 shows that the variables of work environment, leadership style, and self-efficacy explain 87.6% of employee engagement, while the remaining is influenced by other factors outside this study. These findings emphasize the importance of enhancing employee self-efficacy as the main factor in strengthening engagement, and provide practical implications for companies to develop more effective, sustainable human resource management strategies, focusing on improving employee self-confidence and competence.